Micronutrient intakes in 553 Dutch elite and sub-elite athletes: Prevalence of low and high intakes in users and non-users of nutritional supplements - Wardenaar, F.; Brinkmans, N.; Ceelen, I.; Van Rooij, B.; Mensink, M.; Witkamp, R.; De Vries, J. (Nutrients, 2017)
This study investigated whether athletes meet micronutrient recommendations and whether the adequacy of their intake is related to the use of dietary supplements, sport nutrition products or a combination. Micronutrient intakes of 553 Dutch (sub-) elite athletes were assessed using web-based 24-h dietary recalls with accompanying nutritional supplement questionnaires. In the majority of both users and non-users of dietary supplements, vitamin D intake was below the estimated average requirement (AR) if supplements were not included in the analysis. Including dietary supplements improved vitamin D intake, but still a part of the athletes, both men and women, reported an intake below the AR. Non-users of dietary supplements were particularly at risk for low intakes of vitamins B1, B2, B3 and vitamins A, C and selenium. Mean iron intake was reported below the AR in a substantial group of women, both users and non-users. The use of sport nutrition products contributed only slightly to micronutrient intake. A small prevalence of athletes using dietary supplements showed intakes of some micronutrients above the Upper Level. In conclusion, both users and non-users of nutritional supplements reported inadequate intake of micronutrients. For most micronutrients, use of nutritional supplements does not completely compensate for intakes below AR. Athletes should consider making better food choices and the daily use of a low-dosed multivitamin supplement